PENGEMBANGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS E-LEARNING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS MAHASISWA PENDIDIKAN FISIKA PADA MATAKULIAH ASTRONOMI - Rayendra Wahyu Bachtiar (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2013)
Learning for this course is done either face to face or self-employment . Activities undertaken to deliver face- recognition theory and observation of the sky how to use the software as well as the results of previous observations , while self-employment activities are used as a standalone or in groups on the observation of celestial bodies . In addition to face- to-face , students get the material being taught or additional material in the medium of e -learning . Observation of celestial bodies without face to face , then the student gets a sheet works of e -learning and faculty supervision on the activities of student activities with an interactive way directly through the medium of e -learning. Instructional media used is a module , telescope , Stellarium software , video observations of celestial bodies . Always learning activities are integrated with the LMS media e -learning which has been used in university muddy . The presence of media e -learning is needed to study astronomy . In the media provided services for students and for faculty . Lecturers can mengaupload additional material either written or video as an enrichment of students , assignments , worksheets observations of celestial bodies , and quizzes . Students and faculty can interact with the chat service when the observation of celestial bodies independently so that teachers can supervise student activities and student can immediately respond in the event of problems when the observation took place . The method used is the method of research and development ( research and development ) so that this research will generate astronomical lecture material products based e -learning and test the effectiveness of these products . Based on the test results and analysis of data , the conclusions of this study are astronomical learning design can be designed with problem-based learning approach is by way of celestial observation project method . Product astronomy lectures designed teaching materials based e -learning so effective after hours face to face lectures , students can still make access learning through the medium of e -learning .